2014
DOI: 10.1128/jb.01392-13
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Many Charged Residues at the Stator-Rotor Interface of the Na + -Driven Flagellar Motor to Torque Generation in Vibrio alginolyticus

Abstract: In torque generation by the bacterial flagellar motor, it has been suggested that electrostatic interactions between charged residues of MotA and FliG at the rotor-stator interface are important. However, the actual role(s) of those charged residues has not yet been clarified. In this study, we systematically made mutants of Vibrio alginolyticus whose charged residues of PomA (MotA homologue) and FliG were replaced by uncharged or charge-reversed residues and characterized the motilities of those mutants. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 49 publications
0
67
0
Order By: Relevance
“…More than ten MotAB and PomAB stators can assemble around a rotor through the MotA-FliG and PomA-FliG interactions, respectively67891011. The stator is anchored to the peptidoglycan (PG) layer through a well-conserved PG binding motif within the C-terminal periplasmic domain of MotB or PomB121314.…”
mentioning
confidence: 99%
“…More than ten MotAB and PomAB stators can assemble around a rotor through the MotA-FliG and PomA-FliG interactions, respectively67891011. The stator is anchored to the peptidoglycan (PG) layer through a well-conserved PG binding motif within the C-terminal periplasmic domain of MotB or PomB121314.…”
mentioning
confidence: 99%
“…The basal body, which contains the rotor, comprises several ring structures, the L, P, MS, and C rings. The stator, which is an ion-conducting energy-converting complex, surrounds the rotor and generates torque through interaction with components of the rotor [1,2]. The flagellar motor uses mainly two kinds of ions, H + or Na + , as the energy source and the stator is composed of two kinds of membrane proteins.…”
mentioning
confidence: 99%
“…On the other hand, the Na + -driven flagellar motor of marine Vibrio contains such conserved charged residues in PomA and FliG, but single mutations of these conserved residues do not strongly affect the motility [23,24]. Compared with E. coli , the number of conserved charged residues of the flagellar motor in Vibrio is greater, and the contribution of each residue for torque generation may be smaller in Vibrio motor [2,25]. Furthermore, we found that a specific interaction between the charged residues is critical for the correct assembly of the stators around the rotor and is important for torque generation [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MotA has four TM segments, two relatively short segments in the periplasm and two larger segments in the cytoplasm (18). The segment of MotA between TM2 and TM3 contains well-conserved charged residues that engage in electrostatic interactions with charged residues of FliG (19)(20)(21). The Asp-32 regulated conformational change has been shown to affect this rotor-interacting region of MotA (17).…”
mentioning
confidence: 99%